Identification of novel substrates of a disintegrin and metalloprotease 17 by specific labeling of surface proteins. Issue 12 (December 2020) - Omoteyama, Kazuki; Sato, Toshiyuki; Sato, Masaaki; Tsutiya, Atsuhiro; Arito, Mitsumi; Suematsu, Naoya; Kurokawa, Manae S.; Kato, Tomohiro
Abstract: A disintegrin and metalloprotease 17 (ADAM17) catalyzes the cleavage and release of the ectodomains of its substrates at the cell surface in a process termed ectodomain shedding. However, not all ADAM17 substrates have been identified. Here, we used cell surface protein-specific labeling and proteomic approaches to detect and identify ADAM17 substrates. HeLa cell surface proteins were labeled with a fluorescent dye and cultured with or without TAPI-2, an ADAM17 inhibitor. Labeled proteins released into the culture medium were detected by 2-dimensional gel electrophoresis (2DE). Protein spots showing decreased intensity in response to TAPI-2 were selected as substrates of ADAM17 or their binding proteins, and identified by mass spectrometry. ADAM17 knockdown was preformed to examine the behavior of identified proteins. Of 347 proteins detected by 2DE, 49 showed lower intensity in TAPI-2 (+) than in TAPI-2 (-) samples (p < 0.05), and were considered as candidate substrates of ADAM17. Mass spectrometric analysis of 14 protein spots showing >50% decreased intensity identified clusterin as a novel ADAM17 substrate, in addition to known substrates such as desmoglein-2. Western blot analysis showed that ADAM17 knockdown decreased the levels of clusterin fragments cleaved and released from the cell surface. The results identified clusterin as a novel ADAM17 substrate. The method used to identify clusterin could be used to identify the substrates of other sheddases involved in ectodomain shedding. Abstract : ADAM17; Ectodomain shedding; Cell surface protein-specific labeling; Proteomics.